2017
DOI: 10.2528/pierc16120109
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized Volkswagen Logo Uwb Antenna With Slotted Ground Structure and Metamaterial for Gps, Wimax and Wlan Applications

Abstract: Abstract-A novel concept of using slotted ground structure and a single circular split ring resonator (SRR) to achieve multiband operation from a miniaturized UWB antenna is presented in this paper. Initially, a miniaturized Volkswagen logo ultrawideband (UWB) antenna having −10 dB impedance bandwidth of about 124% (2.9-12.4 GHz) in simulation and 116.7% (3.1-11.8 GHz) under measurement is designed. This miniaturization leads to about 10% increment in −10 dB reflection coefficient bandwidth and about 66.71% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Stable radiation characteristics, good impedance matching, and gain are observed when the antenna is fabricated and tested. The simulated and measured results infer that the proposed structure outperforms the traditional antennas studied in the literature …”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Stable radiation characteristics, good impedance matching, and gain are observed when the antenna is fabricated and tested. The simulated and measured results infer that the proposed structure outperforms the traditional antennas studied in the literature …”
Section: Introductionmentioning
confidence: 71%
“…A practically feasible antenna should be compact in size, should offer good radiation characteristics, better gain, and good impedance matching. However, the antennas studied in the literature, lacks the aforementioned properties. The objective of this paper includes the design of a compact quad‐band practically feasible antenna with good gain and stable radiation characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The etching of DGS on the ground plane of an antenna perturbs the current length path, as a result of which the effective capacitance and inductance changes, thereby resulting in antenna miniaturization. Several studies have reported the use of DGS to miniaturize the patch antenna . However, the antenna designed using DGS structure in this research outperforms the antenna studied in literature in terms of size, miniaturization achieved, complexity, and number of operating modes, as illustrated in Table .…”
Section: Introductionmentioning
confidence: 81%
“…This is due to the fact that decrease in the patch size shifts the frequencies to higher resonance. Nevertheless, several miniaturization techniques have been reported in the literature, namely, substrate with high dielectric constant, slotted patch, defected ground structure (DGS), Metamaterials (MTM), magneto‐dielectrics, and so on. However, as compared to the aforementioned miniaturization techniques, slots are easy to implement, are less complex, occupies smaller space, cost‐effective, and have a great relevance in microwave circuit design …”
Section: Introductionmentioning
confidence: 99%